SUPERVISI AKADEMIK: STRATEGI UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI KELAS (STUDI KASUS DI SMA AMKUR SUNGAI PINYUH) - Inviolata Rogo; Marinu Waruwu; Halida; Eny Enawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore the implementation of academic supervision and its impact on learning effectiveness. The method used is qualitative with a case study approach, involving observation, interviews with teachers, supervisors and students, and documentation analysis. The results show that academic supervision is implemented regularly by principals and supervisors, focusing on teaching methods and teacher-student interaction. Supervised teachers experienced improvements in lesson planning and implementation. However, obstacles such as resistance to supervision as a formality and lack of effective follow-up were found. The study recommends improvements in supervision follow-up to optimize its impact on learning effectiveness.